A CASQ1 founder mutation in three Italian families with protein aggregate myopathy and hyperCKaemia. Issue 9 (1st July 2015) - Di Blasi, Claudia; Sansanelli, Serena; Ruggieri, Alessandra; Moriggi, Manuela; Vasso, Michele; D'Adamo, Adamo Pio; Blasevich, Flavia; Zanotti, Simona; Paolini, Cecilia; Protasi, Feliciano; Tezzon, Frediano; Gelfi, Cecilia; et al.
Abstract : Background: Protein aggregate myopathies are increasingly recognised conditions characterised by a surplus of endogenous proteins. The molecular and mutational background for many protein aggregate myopathies has been clarified with the discovery of several underlying mutations. Familial idiopathic hyperCKaemia is a benign genetically heterogeneous condition with autosomal dominant features in a high proportion of cases. Methods: In 10 patients from three Italian families with autosomal dominant benign vacuolar myopathy and hyperCKaemia, we performed linkage analysis and exome sequencing as well as morphological and biochemical investigations. Results and conclusions: We show, by Sanger and exome sequencing, that the protein aggregate myopathy with benign evolution and muscle inclusions composed of excess CASQ1, affecting three Italian families, is due to the D244G heterozygous missense mutation in the CASQ1 gene. Investigation of microsatellite markers revealed a common haplotype in the three families indicating consanguinity and a founder effect. Results from immunocytochemistry, electron microscopy, biochemistry and transfected cell line investigations contribute to our understanding of pathogenetic mechanisms underlining this defect. The mutation is common to other Italian patients and is likely to share a founder effect with them. HyperCKaemia in the CASQ1-related myopathy is common and sometimes the sole overt manifestation. It is likely that CASQ1 mutations may remain undiagnosed if a muscle biopsy is not performed, and the condition could be more common than supposed.